Adoption Behaviour of Orange Growers (Citrus reticulata Blanco ) in Vidarbha Region of Maharashtra - Praveen Gedam, Baldeo Singh, (Indian Journal of Extension Education, 2022)
The present investigation was carried out in the Vidharbha region of Maharashtra. Three districts, namely Nagpur, Amaravati and Wardha were purposively selected and from each district two blocks and from each block two villages were selected randomly and from each village 10 farmers were selected to make 120 samples. The results of study revealed thatmajority of the orange growers adopted 'Nagpur Santra' variety (88.33%), plant spacing (88.33%) followed by Bordeaux paste (88.33%) and bamboo support (78.33%). Most of the orange growers (85.83%) had not adopted seedless variety followed by ventilated corrugated box (83.33%) andmore than 60 per cent orange growers did not adopt recommended herbicides dose (68.33%) for the crop followed by post harvest treatments with fungicides (63.33%) and de greening (62.50%) of oranges. The orange growers found to have medium to high levels of adoption. Size of land and extent of awarenesswere significantly contributing to the adoption of orange growers.